Управління закладом дошкільної освіти на принципах антикризового менеджменту - Мороз-Рекотова, Леся Вікторівна (Видавництво Львівської політехніки, 2023)
The article briefly describes the peculiarities of managing a preschool education institution in war conditions on the basis of the principles of crisis management.
Management of preschool education institution on the principles of of crisis management
Стисло описано особливості управління закладом дошкільної освіти в умовах війни на основі принціпів антикризового менеджменту.
Keywords: управління в умовах війни; принципи антикризового менеджменту; management in times of war; principles of crisis management